Maladaptation beyond a geographic range limit driven by antagonistic and mutualistic biotic interactions across an abiotic gradient. (9th September 2019) - Benning, John W.; Moeller, David A.
Abstract: Species' geographic range limits often result from maladaptation to the novel environments beyond the range margin. However, we rarely know which aspects of the n ‐dimensional environment are driving this maladaptation. Especially of interest is the influence of abiotic versus biotic factors in delimiting species' distributions. We conducted a 2‐year reciprocal transplant experiment involving manipulations of the biotic environment to explore how spatiotemporal gradients in precipitation, fatal mammalian herbivory, and pollination affected lifetime fitness within and beyond the range of the California annual plant, Clarkia xantiana ssp. xantiana . In the first, drier year of the experiment, fitness outside the range edge was limited mainly by low precipitation, and there was some evidence for local adaptation within the range. In the second, wetter year, we did not observe abiotic limitations to plant fitness outside the range; instead biotic interactions, especially herbivory, limited fitness outside the range. Together, protection from herbivory and supplementation of pollen resulted in three‐ to sevenfold increases in lifetime fitness outside the range margin in the abiotically benign year. Overall, our work demonstrates the importance of biotic interactions, particularly as they interact with the abiotic environment, in determining fitness beyond geographic range boundaries.